First Iraqi case of OTUD6B-related disorder: A novel splice-site variant and review of the literature - Saidi, Dalya; Obeidat, Marya (Acta Biomedica Atenei Parmensis, 2026)
OTUD6B-related disorder is a rare autosomal recessive syndrome characterized by intellectual disability, developmental delay, seizures, and dysmorphic features. Since its first description in 2017, fewer than 25 cases have been reported globally. Here, we describe the first genetically confirmed case from Iraq with a novel homozygous splice-site variant in the OTUD6B gene. Whole-exome sequencing (WES) was performed on a 2.5-year-old male presenting with global developmental delay, infantile spasms, microcephaly, dysmorphic facial features, and a ventricular septal defect. Both parents were first cousins. WES identified a novel homozygous splice-site variant in OTUD6B: c.235-3C>G. This variant was absent in gnomAD and 1000 Genomes databases and is predicted to disrupt normal mRNA splicing. The same variant was found in a heterozygous state in both parents. Clinically, the patient shares many hallmark features of OTUD6B-related disorder, including hypotonia, feeding difficulties, ear anomalies, and abnormal dentition. Additional findings in this case include a prominent cartilaginous coccyx, metopic suture craniosynostosis, and reduced visual and auditory acuity, expanding the known phenotypic spectrum. This case confirms the pathogenicity of a novel splice-site variant in OTUD6B and further illustrates the phenotypic variability of OTUD6B-related disorder. It emphasizes the diagnostic value of WES in consanguineous populations and contributes new data to the global understanding of this rare condition.